Arginine Vasopressin Deficiency in Children - A Practical Guide to Etiological Diagnosis and Long-Term Surveillance - Chiara Morreale; Angelica Pisati; Marta Panciroli; Flavia Napoli; Giuseppa Patti; Andrea Rossi; Natascia Di Iorgi; Mohamad Maghnie (The Journal of Clinical Endocrinology & Metabolism, 2026)
Abstract Arginine vasopressin deficiency (AVP-D) is an uncommon but clinically important cause of the polyuria-polydipsia syndrome. Establishing the diagnosis extends beyond confirming hypotonic polyuria and requires differentiation from primary polydipsia and arginine vasopressin resistance, together with identification of the underlying etiology. Unlike adults, children and adolescents with AVP-D frequently present with the earliest manifestation of an evolving neoplastic, infiltrative, inflammatory, congenital, autoimmune, or genetic disorder, making longitudinal clinical, endocrine, and magnetic resonance imaging (MRI) surveillance integral to the diagnostic process. Using three illustrative clinical cases, this review presents a practical approach to the evaluation of AVP-D, integrating clinical assessment, biochemical investigation, dedicated hypothalamic-pituitary MRI, and risk-adapted longitudinal surveillance. We discuss the strengths and limitations of the water deprivation test, the emerging role of copeptin-based diagnostics, and current evidence supporting arginine-, urea-, and glucagon-stimulated copeptin testing. Emphasis is placed on the longitudinal interpretation of MRI, consensus recommendations for PST, and the concept that idiopathic AVP-D should be regarded as a provisional diagnosis requiring continued etiological reassessment. Emerging biomarkers, including neurophysin I and oxytocin, may further refine the assessment of hypothalamic-neurohypophyseal dysfunction but remain investigational in children. Ultimately, AVP-D should be viewed not as the end of the diagnostic process but as its beginning, with clinical assessment, neuroimaging, endocrine evaluation, and structured surveillance integrated to achieve the earliest possible etiological diagnosis.